EFFICACY OF INTRAVITREAL INJECTION OF BEVACIZUMAB IN VITRECTOMY FOR PATIENTS WITH PROLIFERATIVE VITREORETINOPATHY RETINAL DETACHMENT: A Meta-analysis of Prospective Studies. Issue 3 (March 2018) - Zhao, Xin-Yu; Xia, Song; Wang, Er-Qian; Chen, You-Xin
Abstract : Purpose: To evaluate the effect of intravitreal injection of bevacizumab in vitrectomy for patients with proliferative vitreoretinopathy (PVR)-related retinal detachment. Methods: The PubMed, Embase, and the Cochrane Central Register of Controlled Trials were searched from their earliest entries through October, 2016, to identify the studies that had evaluated the effects of intravitreal injection of bevacizumab in vitrectomy for eyes with PVR-related retinal detachment. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were followed. The relevant data were analyzed using Stata 12.0 software. The weighted mean difference, relative risk, and their 95% confidence intervals were used to assess the strength of the association. Results: The authors' search yielded 133 records from which 3 studies that have examined the effects of intravitreal injection of bevacizumab (120 eyes with PVR-related retinal detachment) were included for review and analysis. Their meta-analyses showed that neither the best-corrected visual acuity nor retinal redetachment rate showed any clinically or statistically important difference between the nonbevacizumab and bevacizumab groups ( P > 0.05). In addition, bevacizumab did not influence the interval between vitrectomy and retinal redetachment ( P > 0.05). Conclusion: Based on the available evidence, intravitreal injection of bevacizumab in vitrectomy for patients with PVR-related retinal detachment did not decrease retinal redetachment rate or improve visual acuity. Better-designed studies with larger simple sizes and longer follow-up periods are required to reach valid conclusions regarding benefits and harms. Moreover, evaluation of anti–vascular endothelial growth factor therapy on surgical outcomes in eyes with milder subtypes of PVR or no PVR, but deemed at high risk of PVR, may be worthy of future consideration. Abstract : The effect of intravitreal injection of bevacizumab in vitrectomy for eyes with proliferative vitreoretinopathy–related retinal detachment has been examined in several prospective studies. The authors undertook a systematic review and meta-analysis of the available data to summarize the evidence for ophthalmologists and their patients.